Características de portadores de pterígio na região de Botucatu - Schellini, Silvana Artioli [UNESP]; Veloso, Carlos Eduardo dos Reis [UNESP]; Lopes, Wannessa [UNESP]; Padovani, Carlos Roberto [UNESP]; Padovani, Carlos Roberto [UNESP] (Conselho Brasileiro de Oftalmologia, 2005)
OBJETIVO: Avaliar as características dos portadores de pterígio na região de Botucatu (SP). MÉTODOS: Portadores de pterígio foram avaliados quanto à idade, sexo, profissão, queixas e características da lesão (primário ou recidivado, tamanho, carnoso ou involutivo). Os dados foram submetidos à avaliação estatística. RESULTADOS: Cerca de metade dos portadores eram do sexo feminino, a maioria com idade superior a 40 anos, que procuraram o tratamento com queixa do efeito anti-estético da lesão. A maioria das lesões era primária (77,08%), grau 2 (69,6%) e do tipo carnoso (86,7%). Pterígio grau 4 esteve presente em 1,4% dos pacientes. CONCLUSÃO: Observou-se maior freqüência de portadores de pterígio entre mulheres, acima dos 40 anos e portadoras de pterígio primário, grau 2 e carnoso. A cegueira por pterígio ainda está presente em nosso meio.

PURPOSE: To determine the characteristics of patients with conjunctival pterygia in the Botucatu region (São Paulo State). METHODS: A retrospective study was conducted to evaluate the gender, occupation, complaints and lesion characteristics (primary or recurrent lesion, size, involutive or pulpous) of patients with pterygium. The data were submitted to statistical analysis. RESULTS: Approximately half of the patients were female and over 40 years old. The main complaint was the esthetic effect of the lesion. The majority of the lesions were primary (77.08%), grade 2 (69.6%) and pulpous (86.7%). Pterygium grade 4 was present in the 1.4% of the patients. CONCLUSION: Most patients were female, over 40 years old. Primary, grade 2 and pulpous lesion was the most frequently observed. Blindness caused by pterygium is still present in Brazil.
Characteristics of patients with pterygium in the Botucatu region
Keywords: Pterígio; Prevalência; Incidência; Pterygium; Prevalence; Incidence